If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + -10 = 10x + -3 Reorder the terms: -10 + -5x = 10x + -3 Reorder the terms: -10 + -5x = -3 + 10x Solving -10 + -5x = -3 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -10 + -5x + -10x = -3 + 10x + -10x Combine like terms: -5x + -10x = -15x -10 + -15x = -3 + 10x + -10x Combine like terms: 10x + -10x = 0 -10 + -15x = -3 + 0 -10 + -15x = -3 Add '10' to each side of the equation. -10 + 10 + -15x = -3 + 10 Combine like terms: -10 + 10 = 0 0 + -15x = -3 + 10 -15x = -3 + 10 Combine like terms: -3 + 10 = 7 -15x = 7 Divide each side by '-15'. x = -0.4666666667 Simplifying x = -0.4666666667
| (3x^3-5x^2+7x+5)+4x^2-5x+4= | | tan^4x-2tanx-8=0 | | 8x+108=-4x | | -2(x-6)+7=8(x+6) | | (X^26/Y^10)^-1/2 | | Ln(3x-19)=8 | | 3/4*3.14*512 | | 6x-18=5x-16 | | 3a+9=15 | | 9x^2+40x=25 | | 18-9w= | | 4z/-12=8 | | e(x-2)=7 | | 9[9-(-8x-9)]=648x+810 | | 10x^2+84x+185=0 | | -ax=b-c | | -y+42-3y=6 | | (2p-1)(p+3)-(7p+4)(p+3)= | | 1/3-4=-y | | 3=3(2x-4)-3(4x+4)-10 | | 36r^2-121= | | ln(6)+ln(x)=ln(6x) | | 42a^2+a-30=0 | | 6a^2-28a+16= | | 28/5 | | 36=b(5)(6) | | (B/9)-.5=(5/18) | | (x)(-3)-4=-10 | | 81x+36x+20=0 | | (3x^-5/8y^-7)^-2 | | 0=20t-5(t^2)+25 | | 4x-3/8 |